1960
DOI: 10.1029/jz065i010p03107
|View full text |Cite
|
Sign up to set email alerts
|

The radiation belt produced by neutrons leaking out of the atmosphere of the Earth

Abstract: The experimental information about the radiation belt is summarized. Calculations of the radiation belt spectra and fluxes based on the neutron decay source are compared with the experiments. The purpose is to find out in what ways the neutron decay source explains the observed features of the radiation belt and where other sources may be needed. The conclusion reached is that the inner zone of the radiation belt is quite likely supplied by neutron decay alone and also the e2 region of the outer zone may well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1961
1961
1966
1966

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The beta decay electrons from neutrons certainly contribute to the outer belt [Hess, 1960;Dessler and Karplus, 1960]. Recently, however, it was shown that processes other than injection of neutron decay electrons must be operative in order to account for the spatial distribution of electrons in the outer belt [Hess, Killeen, Fan, Meyer, and Simpson, 1961].…”
Section: Parameters For Electron Flux and Energy Density Inmentioning
confidence: 99%
“…The beta decay electrons from neutrons certainly contribute to the outer belt [Hess, 1960;Dessler and Karplus, 1960]. Recently, however, it was shown that processes other than injection of neutron decay electrons must be operative in order to account for the spatial distribution of electrons in the outer belt [Hess, Killeen, Fan, Meyer, and Simpson, 1961].…”
Section: Parameters For Electron Flux and Energy Density Inmentioning
confidence: 99%
“…Vew little is known about the source of the radiation, although three general origins have been discussed. They are, first, the injection of electrons into the trapping region from the decay of cosmic-ray albedo neutrons [Hess, 1960]; second, the direct injection of electrons into the trapping region from solar gas clouds; and last, the local acceleration of low-energy electrons present in the exosphere or from the solar stream [Van Allen and F•'a•k, 1959b; A•'noldy, Ho#man, and Winckle•', 1960b]. It is possible that all the above-mentioned sources, and perhaps even some that have not been considered, contribute to the intensity of the radiation.…”
Section: Because the Prop/gm And Scint/gm Ratio Curves Rise When Fiatmentioning
confidence: 99%
“…and Hess [1960] have proposed that the relative minimum in the outer belt as measured by radiation detectors aboard Explorer VI earth satellite is caused by a predominantly low-altitude injection from neutron albedo decays and a local loss of particles when those with low mirror points drift through the Capetown magnetic anomaly. To the contrary, this note will show, assuming the validity of present magnetic data, that any particles affected by the Capetown anomaly do not have trajectories that would pass through the position of the observed minimum in the outer belt.…”
Section: Dessler and Karplusmentioning
confidence: 99%
“…The effect of the Capetown magnetic anomaly on the motion of trapped particles has been thoroughly discussed by Dessler [1959] and Dessler and Karplus [1960], and therefore will not be repeated here. Hess [1960] and Hess and Killeen [1960] have calculated that the depth of the gap as it would be seen by radiation detectors, assuming a neutron source injection, to be The particles that would have mirror points below about 1300 km over the anomaly are of interest because at this altitude they begin to be rapidly scattered into the atmosphere. The locus of the mirror points of these particles must be followed as they drift in longitude around the earth to 148øE longitude.…”
Section: B Capetown Magnetic Anomaly and Particle Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation